If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 5x = x + 1 + 5x Reorder the terms: -6 + 5x = 1 + x + 5x Combine like terms: x + 5x = 6x -6 + 5x = 1 + 6x Solving -6 + 5x = 1 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -6 + 5x + -6x = 1 + 6x + -6x Combine like terms: 5x + -6x = -1x -6 + -1x = 1 + 6x + -6x Combine like terms: 6x + -6x = 0 -6 + -1x = 1 + 0 -6 + -1x = 1 Add '6' to each side of the equation. -6 + 6 + -1x = 1 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = 1 + 6 -1x = 1 + 6 Combine like terms: 1 + 6 = 7 -1x = 7 Divide each side by '-1'. x = -7 Simplifying x = -7
| 2(x+7)-15=-3(-4x+2)-17x | | 270000+1000x=1500x | | f(x)=79-5x-2 | | -13m-20=-6m+1 | | tx=23b(a-9) | | 95=c+-832 | | 21(5m+19)=21(6m+12) | | -5y-8(4y-6)=1+3(9-y) | | 4w(3)= | | 9x=4+32 | | 17x-11y=-1 | | y=.5cos(2X) | | -6a+3=-3(2a-1)-5 | | 3x+5-3=x-8 | | -3u+2=10u+30 | | -7a+4=-11a | | 88=5+6w | | 3x^2-2-5=0 | | 7x+12=2x-13 | | P=2(2w)+5+2w | | 6(w-8)+4=-12 | | 3+5u=-22 | | -3(2+x)=x+8 | | -10e-9y-4+3e-10y-7= | | 7-12d=41 | | 3(2x+1)+2(x+4)=29 | | 12.5+4x-f=4x+3-x | | 3(2x+1)+2(x+4)=19 | | -10=(8y-12) | | 2y+12=36 | | 2(x+5)=5x-7-3x | | 0=x^3+4x^2-11x+6 |